Ten Year Groundwater Simulation in Merapi Aquifer, Sleman, DIY, Indonesia - Visi Asriningtyas; Doni Prakasa Eka Putra (Faculty of Geography, Universitas Gadjah Mada, 2006)
Simulation of groundwater withdrawal has been conducted with a groundwater modeling system (GMS) version 3.1 software at a regional scale. The simulation was conducted from ten year groundwater withdrawal data in Merapi Aquifer, DIY, Indonesia, for two assumed scenarios, with an emphasis in Sleman area. The result for the ten year groundwater simulation was conducted spatially distributed in the Merapi Aquifer after the steady state simulation was reached. With two different types of transient simulations, the total withdrawal of 28,968 m3/day for the whole Merapi Aquifer is still acceptable with caution, as long as the . recharge is not decreasing. However, less withdrawal as the existing withdrawal condition is recommended until local site investigation is sufficient to avoid the danger of overdraft.